Unusual pattern of chikungunya virus epidemic in the Americas, the Panamanian experience. - Jean-Paul Carrera; Yamilka Díaz; Bernardino Denis; Itza Barahona de Mosca; Dennys Rodriguez; Israel Cedeño; Dimelza Arauz; Publio González; Lizbeth Cerezo; Lourdes Moreno; Lourdes García; Lisseth E Sáenz; et al. (Public Library of Science (PLoS), 2017)
BACKGROUND:Chikungunya virus (CHIKV) typically causes explosive epidemics of fever, rash and polyarthralgia after its introduction into naïve populations. Since its introduction in Panama in May of 2014, few autochthonous cases have been reported; most of them were found within limited outbreaks in Panama City in 2014 and Puerto Obaldia town, near the Caribbean border with Colombia in 2015. In order to confirm that Panama had few CHIKV cases compared with neighboring countries, we perform an epidemiological analysis of chikungunya cases reported from May 2014 to July 2015. Moreover, to understand this paucity of confirmed CHIKV cases, a vectorial analysis in the counties where these cases were reported was performed. METHODS:Chikungunya cases were identified at medical centers and notified to health authorities. Sera samples were analyzed at Gorgas Memorial Institute for viral RNA and CHIKV-specific antibody detection. RESULTS:A total of 413 suspected cases of CHIKV infections were reported, with incidence rates of 0.5 and 0.7 per 100,000 inhabitants in 2014 and 2015, respectively. During this period, 38.6% of CHIKV cases were autochthonous with rash and polyarthralgia as predominant symptoms. CHIKV and DENV incidence ratios were 1:306 and 1:34, respectively. A phylogenetic analysis of E1/E2 genomic segment indicates that the outbreak strains belong to the Asian genotype and cluster together with CHIKV isolates from other American countries during the same period. Statistical analysis of the National Vector Control program at the district level shows low and medium vector infestation level for most of the counties with CHIKV cases. This index was lower than for neighboring countries. CONCLUSIONS:Previous training of clinical, laboratory and vector workers allowed a good caption and detection of the chikungunya cases and fast intervention. It is possible that low/medium vector infestation level could explain in part the paucity of chikungunya infections in Panama.